PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI CANVA TERHADAP HASIL BELAJAR SISWA KELAS V MATA PELAJARAN IPAS MATERI KENAMPAKAN ALAM DI SDN PABIAN IV - Farwah Al-ifrah; Tri Sukitman; Iwan Kuswandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low learning outcomes of students on natural appearance materials, which is caused by the lack of use of interactive learning media that is relevant to student needs. This study aims to analyze the influence of Canva application-based interactive learning media on the learning outcomes of grade V students at SDN Pabian IV. The method used is quantitative using one group pretest-posttest design. The research sample consisted of 21 students in class V who were selected purposively. Data was obtained through learning outcome tests before (pre-test) and after (post-test) the use of Canva learning media. Data analysis includes normality tests and paired t-tests to determine the distribution of data and the significance of differences in learning outcomes. The results showed that the average pre-test score was 69.52 with a minimum score of 30 and a maximum of 100, while the average post-test score increased to 77.62 with a minimum score of 50 and a maximum of 100. The normality test showed that the pre-test and post-test data were normally distributed, with significance values of 0.298 and 0.118 (p > 0.05), respectively. The t-test produced a significance value of 0.000 (p < 0.05), which indicates a significant improvement in learning outcomes after the use of Canva media. This study concludes that interactive learning media based on the Canva application is effective in improving student learning outcomes on natural appearance materials. The use of this media can be an innovative alternative for learning that is more interesting and relevant to technological developments.